1988
DOI: 10.1111/j.1365-2133.1988.tb07102.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic protoporphyria exacerbated by oral iron therapy

Abstract: Four patients with erythropoietic protoporphyria (EPP) are reported, in whom oral iron produced clear-cut clinical and biochemical deterioration. This suggests that there are two biochemically and genetically distinct sub-groups of EPP patients distinguished by their dramatically different response to oral iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…Moreover, if iron supplementation is beneficial in EPP, an iron deficit can be assumed. In the medical literature there are conflicting case reports on the effect of iron supplementation on EPP symptoms [4,18,27,31]. In our clinical experience, iron supplementation has consistently exacerbated EPP phototoxic symptoms, although it may improve the general well-being of the patients, increase their hemoglobin concentrations and thus ameliorate their anemia.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, if iron supplementation is beneficial in EPP, an iron deficit can be assumed. In the medical literature there are conflicting case reports on the effect of iron supplementation on EPP symptoms [4,18,27,31]. In our clinical experience, iron supplementation has consistently exacerbated EPP phototoxic symptoms, although it may improve the general well-being of the patients, increase their hemoglobin concentrations and thus ameliorate their anemia.…”
Section: Discussionmentioning
confidence: 71%
“…However, results of this approach in patients with EPP are contradictory. It has been reported that iron therapy may exacerbate hepatic dysfunction [48,49] whereas in some case reports the correction of iron deficiency has improved EPP [50,51] . Nevertheless, the mechanism of this favorable response to iron therapy remains unknown, so more studies with a significant number of patients are necessary to clarify the role of iron therapy in the medical treatment of EPP.…”
Section: Parenteral Iron and Transfusion Of Erythrocytesmentioning
confidence: 98%
“…35,36 Interestingly, in some EPP patients, the disease is exacerbated by oral iron therapy. [37][38][39] In EPP, the erythroid program functions normally except that diminished levels of ferrochelatase result in less than stoichiometric conversion of protoporphyrin to heme. Because anemia is generally not a feature of EPP, it is clear that sufficient levels of heme are eventually synthesized.…”
Section: Org Frommentioning
confidence: 99%